PERAN WANITA BEKERJA DALAM RUMAH TANGGA - Syam, Syahrianti (An - Nisa`, 2011)
Career women are the ones who serve husband and children as well as work to support livelihood. Hence, it implies that career women provide multi-function in the family namely to educate and to work. Working women also play a role in child- rearing patterns and patterns decision making employe in the housewives. There are many types of child-rearing pattern of parents to their children namely permissive parenting, authoritarian parenting, democracy parenting and careless parenting. Parents need to learn to apply positive parenting on children in order to form the positive character of children in the future. Role working women in pattern of parents to their children arcd patterns decision making employe in the housewives can be conducted by using the approach of structural functionalism and symbolic interactionalism. In solving a problem parents should play an important role in guiding their children to take a decision.